Recent Advances in Metal Chalcogenide Quantum Dots: From Material Design to Biomedical Applications. (11th August 2022) - Piao, Zhiyan; Yang, Dan; Cui, Zhongjie; He, Haiyang; Mei, Shiliang; Lu, Hanxu; Fu, Zizhao; Wang, Le; Zhang, Wanlu; Guo, Ruiqian
Abstract: With the rapid progress in nanomaterials and biochemistry, there has been an explosion of interest in biomolecule‐modified quantum dots (QDs) for biomedical applications. Metal chalcogenide quantum dots (MCQDs), as the most widely studied QDs, have attracted tremendous attention in the biomedical field on account of their unique and excellent optical properties and the ease of biomolecular modifications. Herein, important advances in MCQDs over recent years are reviewed, from materials design to biomedical applications. Especially, this review focuses on the challenges encountered in the applications of MCQDs in biomedical fields and how these problems can be solved by rational design of synthesis methods and modifications, which have opened a universal route to develop the functionalized MCQDs. Moreover, recent processes in bioimaging, biosensing, and cancer therapy based on MCQDs are examined, including the rapid detection and diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). This review provides broad insights into MCQDs in the biomedical field and will inspire material researchers to develop MCQDs in the future. Abstract : In this review, the properties and rational material design of metal chalcogenide quantum dots (MCQDs) from synthesis to modifications are introduced. Then, the recent progress of biomedical applications based on modified MCQDs, including bioimaging, biosensing, and cancer therapy is summarized, which provides valuable guidance to design MCQDs for biomedical applications.